Fourier Transform and Photoacoustic Absorption Spectra of Ethylene within 6035–6210 cm−1: Comparative Measurements. (17th May 2010) - Kapitanov, Venedikt A.; Solodov, Alexander M.; Petrova, Tatiana M.; Ponomarev, Yurii N.
Abstract : Measurements of ethylene absorption spectra with Fourier Transform (FT) and Photoacoustic (PA) spectrometers within 6035–6210cm − 1 are described. The methodology used for building the frequency scale for both spectrometers is presented. The methane absorption spectrum, included into the HITRAN database, was used in both cases to calibrate the frequency scale. Ethylene absorption spectra were obtained with the two recording methods; a coincidence of the measured line center positions was obtained with an accuracy of 0.0005cm − 1 .